Individual learning and building organisational capacity for development - Johnson, Hazel; Thomas, Alan (2007)
Building capacities and capabilities for international development is an ongoing subject for debate, further fuelled by recent interest in learning and knowledge. This article focuses on how, and the extent to which, individual learners in education and training programmes for development policy and management interact with their organisations to build capacities and capabilities. It demonstrates some of the ways that individual learning and organisational capacity are linked by examining case studies from Uganda. Zimbabwe and South Africa. The article reflects on the complex nature of this interaction and on the broader challenges of linking learning to development. - Reproduced.
Keywords: Organizations